Dinamika Lembaga Pendidikan Mempertahankan Eksistensi Pada Era Kompetitif - Qori Kartika (El-Idare, 2017)
This article aims to reveal and reinforce the importance of educational institutions in maintaining their existence. This period, the number of emerging new educational institutions with new concepts and approaches they offer. This makes the old educational institution faced with a critical position, if it does not adapt to the demands of the environment. This article uses a literature study to examine the issues of educational institutional measures to deeply retain existence. The results of the study show that such rapid environmental changes can no longer be overcome by the natural processes of institutional development and "flowing with the flow". It is necessary to design the development to realize planned changes so that the institution can grow in a positive direction and be able to face the environment. However, an important note in the process of institutional development, the winners are those who have a better strategy. Therefore, to achieve the goals in the process of institutional development is required ketapatan selected strategy.